2023
DOI: 10.3389/fphar.2023.1219980
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of 9-phosphorylated acridine as butyrylcholinesterase inhibitors with antioxidant activity and the ability to inhibit β-amyloid self-aggregation: potential therapeutic agents for Alzheimer’s disease

Abstract: We investigated the inhibitory activities of novel 9-phosphoryl-9,10-dihydroacridines and 9-phosphorylacridines against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and carboxylesterase (CES). We also studied the abilities of the new compounds to interfere with the self-aggregation of β-amyloid (Aβ42) in the thioflavin test as well as their antioxidant activities in the ABTS and FRAP assays. We used molecular docking, molecular dynamics simulations, and quantum-chemical calculations to explain ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Earlier, we had investigated such a phenomenon with MD simulations. [ 71,90 ] It was observed that the nonprotonated form maintains interactions by bridging water molecules with the same group as a protonated form. Namely, with the main chain oxygen atom of Trp86 in the case of binding to AChE (Figure 2a) and Leu286 for BChE (Figure 2b; in both figures, water molecules are not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we had investigated such a phenomenon with MD simulations. [ 71,90 ] It was observed that the nonprotonated form maintains interactions by bridging water molecules with the same group as a protonated form. Namely, with the main chain oxygen atom of Trp86 in the case of binding to AChE (Figure 2a) and Leu286 for BChE (Figure 2b; in both figures, water molecules are not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we had investigated such a phenomenon with MD simulations. [71,90] It was observed that the nonprotonated form maintains interactions by bridging water molecules with the same group as a protonated form.…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%